The Practical Use of Online Comic Manga: Facilitating Students’ English Reading Engagement - Nurul Lailatul Khusniyah (STAI Hubbulwathan Duri, 2021)
The study was done to get the depth information from the practical use of online comic manga in building students’ English reading engagement. It creates the enjoy time to read and students get the meaningful activity in each reading process. The method used the one-group pretest-posttest experimental design. The data collected through observation, documentation and reading test. While data analysis used the t-test paired two samples for means. The resulting shows that t-stat (9.2934) t-table (2.0484), It means that reading online comic manga gave the fun activity at online class or home. The implication of the study was on the reading source learning to create enjoy and comfort learning.